The Effects of Online Health Promotion to New Habit Adaptation - Ni Putu Widya Sulasmi; Dian Lesia; Sri Ariwati; Agus Widhi Adnyana; Garniswari Garniswari; Ari Irawati; Gunantari Gunantari; Wayan Darsana (Universitas Muhammadiyah Surakarta, 2022)
Health workers have a high risk of being exposed to COVID-19. The lack of knowledge of health workers, especially nurses, can lead to increased stress during the pandemic. Therefore, there is a need for preventive and promotive efforts in the form of new habit adaptation. Online health promotion can be used to improve public health optimally. The purpose of this study was to determine the effect of health promotion on new health adaptation which was conducted online. The research design used pre-experimental with one group pre-post test design. Nurses at the Bali Provincial Mental Hospital who have attended the Mental Health and Psychosocial Support (DKJPS) training on adapting new habits online for 3 days were given a pretest on the first day of implementation of new habit adaptation and a post test on the 56th day. The samples used were 82 nurses and 146 nuclear family nurses who were selected using purposive sampling that met the inclusion criteria, that is nurses from the Bali Province Mental Hospital and their nuclear families aged 15 years. Data collection was carried out from August 25, 2021 to October 26, 2021 using the New Habit Adaptation questionnaire in reference to the DKJPS manual book. The analysis used the Wilcoxon Sign Rank Test. The results of the analysis showed that the p value value 0.05 showed that there was an effect of online health promotion on the new habit adaptation. The results of this study prove that online health promotion affects the implementation of new habit adaptation in an effort to prevent the transmission of COVID-19.